Pharmaceutical Preparation Formulation and Innovation in Active Substance Delivery Technology of Premna serratifolia: Literature Review - isnindar isnindar; rise desnita (Program Studi Farmasi, Universitas Ma Chung, 2026)
Background: The Premna serratifolia L. plant is a botanical resource rich in potential secondary metabolites for development into modern pharmaceutical preparations. Over the last decade (2016-2026), research has progressed rapidly from conventional topical formulations to more sophisticated drug delivery systems to overcome the stability issues of active substances. Objective: To systematically review various pharmaceutical formulations of Premna serratifolia leaves and evaluate their biological efficacy based on the latest original studies. Methods: Over the previous 10 years, original scientific literature from reliable databases like Science Direct and Google Scholar was reviewed. Results: Various preparations have been successfully optimized, including a peel-off gel mask with antioxidant activity reaching 77.20%, a sunscreen lotion with an ultra SPF value of up to 34.60, and an anti-inflammatory cream combined with sappanwood. Recent delivery technology innovations include Ethocel/Eudragit polymer-based microparticles with a size of 1.024-1.662 µm, and excellent antibacterial potential is demonstrated by biosynthesized silver nanoparticles (AgNPs). Conclusion: P. serratifolia exhibits high formulation flexibility for cosmetic and therapeutic applications, although standardization of marker compounds and validation through human clinical trials remain major challenges for future development.